The aqueous alteration of GEMS-like amorphous silicate in a chondritic micrometeorite by Antarctic water. (15th January 2021) - Suttle, M.D.; Folco, L.; Genge, M.J.; Franchi, I.A.; Campanale, F.; Mugnaioli, E.; Zhao, X.
Abstract: We analysed the heterogenous fine-grained (sub-μm) matrix of a small (58 × 93 μm), unmelted and minimally heated (<350 °C) micrometeorite (CP94-050-052) recovered from Antarctic blue ice. This particle contains some unaltered highly primitive phases, including refractory anhydrous high-Mg silicates and submicron crystalline needle-shaped acicular grains interpreted as enstatite whiskers. The particle also contains an abundance of micron-sized Fe-rich grains, which span a compositional and textural continuum between amorphous oxygen-rich silicate and poorly crystalline Fe-rich phyllosilicate (cronstedtite). These Fe-rich grains are here interpreted as secondary phases formed by aqueous alteration. Their inferred anhydrous precursors were likely primitive "GEMS-like" amorphous Fe-Mg-silicates. This micrometeorite's bulk chemical composition and mineralogy suggest either a carbonaceous chondrite or cometary origin. However, the particle's average O-isotope composition (δ 17 O: −12.4‰ [±5.0‰], δ 18 O: −24.0‰ [±2.3‰] and Δ 17 O at +0.1‰ [±4.8‰] is distinct from all previously measured chondritic materials. Instead this value is intermediate between primitive chondritic materials and the composition of Antarctic water – strongly implying that the particle was heavily affected by Antarctic alteration. Analysis of the micrometeorite's H-isotopes reveals low deuterium abundances (δD: −217‰ to −173‰ [±43–47‰]) paired with high H abundances (and thus high water contents [<25 wt.%]). Although both water contents and H-isotope compositions overlap with those reported in CM chondrites, the datapoints measured from CP94-050-052 extend to more extreme values. Further supporting the idea that the aqueous alteration that affected this micrometeorite operated under different environmental conditions to asteroidal settings. These data collectively demonstrate partial isotopic exchange with light (δ 18 O-poor, δD-poor) terrestrial fluids whilst the micrometeorite resided in Antarctica. Although this micrometeorite may have been aqueously altered whilst on its parent body this cannot be conclusively demonstrated due to the extent of the weathering overprint. Antarctic alteration operated at significantly higher water-to-rock ratios than chondritic settings. Despite these differences the extent of secondary replacement and the duration of alteration were limited with mafic silicates remaining unaffected. The combined alteration conditions for this particle likely operated over short timescales (<24 h), under mildly alkaline conditions (∼pH 8) and at low temperatures (<50 °C), this could have occurred during the micrometeorite's extraction from blue ice.